Rating małych i średnich przedsiębiorstw - Bielawska, Aurelia (Rating of Small and Medium-Sized Enterprises, 2006)
In the article the nature of rating is explained and furthermore an own definition of this issue is made. The advantages of the rating throughout the enterprises are shown as well as the characteristics of small and medium-sized enterprises as subjects of the rating. The need for the development of the algorithms of rating that suit to the structural characteristics of such enterprises is explained too. There is a proposition that the financial institutions should give rating marks for the small and medium-sized enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 75-82